President's Message for 1968 - Dale, Ernest (Academy of Management Journal, 1968)
The article discusses the plans of the Academy of Management in 1968, announcing that Paul Gordon was appointed as president-elect and Joseph Litterer as vice-president. The author states that he hopes the organization can stimulate industrial interest in the progress of management thought, and he calls for members of the Academy of Management to keep up personal relationships as the membership of the group grows. The author states that he plans to present a reexamination of current management theory and practice at regional meetings.